Kinetics and modelling of thiosulphate biotransformations by haloalkaliphilic Thioalkalivibrio versutus - Hajdu-Rahkama, Reka; Ozkaya, Bestamin; Lakaniemi, Aino-Maija; Puhakka, Jaakko A. (ELSEVIER SCIENCE SA, 2020)
Biotransformation of thiosulphate by Thioalkalivibrio versutus was studied under haloalkaline conditions (pH 10, 0.66-1.2 M Na+) using batch assays and modelling tools for possible sulphur recovery from haloalkaline industrial streams. The thiosulphate was fully biotransformed to sulphate or to sulphate and elemental sulphur at initial S2O32--S concentrations of 25-550 mM within 10 days. The highest biotransformation rate of 2.66 mM [S2O32--S] h(-1) was obtained at initial S2O32--S concentration of 550 mM with half saturation constant (K-s) of 54.5 mM [S2O32--S]. At initial concentrations below 100 mM S2O32--S, the main product was sulphate whilst at above 100 mM also elemental sulphur was produced with up to 29% efficiency. The model approach developed incorporated S2O32- biotransformation to SO42- and S-0. The kinetic modelling results were compatible (R-2 > 0.90) with the experimental data. The maximum growth rate (mu(m)) was 0.048 h(-1) (0.47 mM C(5)H(7)NO(2)h(-1)) and the maximum growth yield 0.18 mM C5H7NO2/mM S2O32--S (20 g cell/mol S2O32--S). The high rate thiosulphate biotransformation and elemental sulphur recovery results together with the developed kinetic model can be used for bioprocess design and operation. The potential industrial applications would aim at sustainable resource recovery from industrial haloalkaline and sulphurous process and/or effluent streams.
Keywords: Thioalkalivibrio versutus; Haloalkaliphilic sulfur oxidizing bacteria; Thiosulfate biotransformation; Sulfur disproportionation; Resource recovery; Kinetics; SULFUR-OXIDIZING BACTERIA; LEPTOSPIRILLUM-FERRIPHILUM; DRIVEN DENITRIFICATION; IRON OXIDATION; SULFIDE; GROWTH; PH; REMOVAL; Engineering